2017
DOI: 10.5152/eurasianjmed.2017.17046
|View full text |Cite
|
Sign up to set email alerts
|

Functional Effects of Alagebrium (ALT-711)–Isolated Rat Carotid Artery

Abstract: Objective: In our study, the effects of glycosylated protein cross-link breaker, alagebrium was investigated on isolated rat carotid artery using myography. Alagebrium showed vasodilator effect on carotid artery rings; particularly, this effect was significantly increased in endothelium-intact rings. Materials and Methods:To clarify the vasodilator mechanism of alagebrium, different antagonists such as N(G)-Nitro-L-arginine methyl ester (L-NAME), glibenclamide, indomethacin, metoprolol, propranolol, tetraethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…Aortic segments were incubated under standard conditions (37 °C, 5% CO 2 , 20% O 2 , humidified) for 72 hours in culture medium alone (vehicle; DMEM supplemented with 10% fetal calf serum and 1% penicillin-streptomycin) or with the addition of 30 µmol/L TMAO (Sigma-Aldrich Corp), the average concentration measured in plasma from the dietary supplementation intervention. Vehicle- and TMAO-treated segments from a subset of mice were also treated with the AGEs inhibitor alagebrium 35–37 (N=5; 2 mmol/L; AstaTech, Inc, Bristol, PA) or the superoxide dismutase mimetic 4-hydroxy-2,2,6,6-tetramethylpiperidin-1-oxyl (TEMPOL; N=5 mice; 100 μmol/L; Sigma-Aldrich, Corp) to suppress reactive oxygen species (ROS) production. Following the incubation, stress-strain testing was performed to assess intrinsic mechanical stiffness.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aortic segments were incubated under standard conditions (37 °C, 5% CO 2 , 20% O 2 , humidified) for 72 hours in culture medium alone (vehicle; DMEM supplemented with 10% fetal calf serum and 1% penicillin-streptomycin) or with the addition of 30 µmol/L TMAO (Sigma-Aldrich Corp), the average concentration measured in plasma from the dietary supplementation intervention. Vehicle- and TMAO-treated segments from a subset of mice were also treated with the AGEs inhibitor alagebrium 35–37 (N=5; 2 mmol/L; AstaTech, Inc, Bristol, PA) or the superoxide dismutase mimetic 4-hydroxy-2,2,6,6-tetramethylpiperidin-1-oxyl (TEMPOL; N=5 mice; 100 μmol/L; Sigma-Aldrich, Corp) to suppress reactive oxygen species (ROS) production. Following the incubation, stress-strain testing was performed to assess intrinsic mechanical stiffness.…”
Section: Methodsmentioning
confidence: 99%
“…Trimethylamine N-Oxide and Aortic Stiffness measured in plasma from the dietary supplementation intervention. Vehicle-and TMAO-treated segments from a subset of mice were also treated with the AGEs inhibitor alagebrium [35][36][37] (N=5; 2 mmol/L; AstaTech, Inc, Bristol, PA) or the superoxide dismutase mimetic 4-hydroxy-2,2,6,6-tetramethylpiperidin-1-oxyl (TEMPOL; N=5 mice; 100 μmol/L; Sigma-Aldrich, Corp) to suppress reactive oxygen species (ROS) production. Following the incubation, stress-strain testing was performed to assess intrinsic mechanical stiffness.…”
Section: Brunt Et Almentioning
confidence: 99%
“…), so changes in cooking habits and methods can help to reduce the accumulation of AGEs in the body [79]. Toprak et al [80] observed that the mechanism of the diastolic effect of alagebrium (ALT-711) on carotid arteries in healthy animals is not only to reduce the cross-linking of AGEs with collagen but that ALT-711 has the ability to improve the uptake and release of Ca 2+ from the sarcoplasmic reticulum of cardiac myocytes. Some studies have shown that the angiotensin II receptor blockers telmisartan and losartan inhibit endogenous AGE production in cultured cells in vitro [81].…”
Section: Advanced Glycation End Productsmentioning
confidence: 99%
“…15 Alagebrium (ALA) was the primary drug originally introduced to break the covalent bonds formed in crosslinked proteins, in order to maintain the normal function of these proteins after being detached, and even if rebonding occur, ALA can also break up these bonds again, so reducing the tissue levels of AGEs and ameliorating their hazardous effects. 16,17 Metformin (MF) the most commonly prescribed drug for diabetes mellitus type 2 (DM-2), works by decreasing absorption of glucose from the intestine, enhancing peripheral glucose uptake, lowering fasting plasma insulin and enhancing insulin sensitivity, 18 leading to the reduction in blood glucose without causing hypoglycemia, MF can also inhibit gluconeogenesis through the activation of AMP-activated protein kinase (AMPK), which is an important energy metabolism regulator. 19 Besides, the glucose-lowering action of MF, it improves other features of MS, not only by improving the insulin sensitivity in liver and muscle 18 but also by its beneficial hypolipidemic, antioxidant, cardio-protective and anti-inflammatory actions.…”
Section: Introductionmentioning
confidence: 99%